Research of the Lapping Burn and Inhibition of Hypoid Gear - Liu Xianghuan; Liu Defu; Chen Tao; Zhang Yu (Jixie chuandong)
It often happens to tooth surface burn of hypoid gears installed on automobile drive axle during the gear lapping process,it will cause pitting,peeling and cutting. The discrimination method of lapping burn is presented by describing the features of burn location. The effect on gear durability caused by lapping burn is analyzed by studying the metallographic structure and the hardness variation and the effect is verified by rig test and road test. By establishing the mathematical model of the hypoid gear meshing point relative sliding and by calculating the relative sliding speed of each meshing point,it’s found that the burned area of tooth surface is the biggest relative sliding velocity. The reproducibility tests are down by several times of tests for lapping burn. It’s verified that the main factor in lapping burn is closely related to the lapping clearance control. Combining with the production practice experience,several methods to control the lapping burn are presented through revising operation standard,lapping clearance automatic monitoring,etc.